Peran Public Relations di Kantor Walikota Jakarta Timur Menggunakan Media Sosial Instagram dalam Membangun Citra Institusi - Tasya Putri Choirunnisa; A.Yuda Triantanto; Dhefine Armelsa (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
What is the role of Public Relations in the East Jakarta Mayor's Office Using Instagram Social Media in Building an Institutional Image, the researcher will conduct research using a descriptive method with a qualitative approach. Data collection techniques in this research were interviews, observation and documentation studies. The results of this research are that using social media Instagram can build the image of an institution and help the role of public relations in the East Jakarta Mayor's Office.